Management of the Implementation of the Merdeka Curriculum at Madrasah Aliyah (Analysis of the Roles of the Head of Madrasah and Teachers in Strengthening Student Competencies) - Irfan Moch Noor; ⁠Baidi; Imam Sukardi (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze the management of the implementation of the Merdeka Curriculum at Madrasah Aliyah, focusing on the roles of the principal and teachers in strengthening student competencies. The curriculum transformation requires madrasahs to carry out managerial adjustments encompassing comprehensive planning, organizing, implementation, and evaluation of the curriculum. This research uses a descriptive qualitative approach with data collection techniques including in-depth interviews, observation, and documentation. The research subjects include the principal, vice principal for curriculum affairs, subject teachers, and students. The results reveal that the principal actively performs managerial functions through the development of curriculum work programs, formation of curriculum teams, academic supervision, and guiding teachers in preparing teaching modules. Meanwhile, teachers play a crucial role in designing differentiated learning, implementing project-based learning, and applying authentic assessments to measure students’ competency development. The implementation of the Merdeka Curriculum has had a positive impact on increasing student participation and creativity, although challenges remain, such as teachers’ limited digital literacy, variation in the quality of teaching modules, and unequal learning facilities. Overall, the study concludes that the success of Merdeka Curriculum implementation is highly determined by the visionary leadership of the principal and the pedagogical readiness of teachers to create a flexible, collaborative, and contextual learning process. The study’s recommendations include the need for advanced training, strengthening digital facilities, and ongoing evaluations to ensure improved learning quality in madrasahs.